1995
DOI: 10.1128/mcb.15.8.4585
|View full text |Cite
|
Sign up to set email alerts
|

A Skeletal Muscle-Specific Enhancer Regulated by Factors Binding to E and CArG Boxes Is Present in the Promoter of the Mouse Myosin Light-Chain 1A Gene

Abstract: The mouse myosin light-chain 1A (MLC1A) gene, expressed in the atria of the adult heart, is one of the first muscle genes to be activated when skeletal as well as cardiac muscles form in the embryo. It is also transcribed in skeletal muscle cell lines at the onset of differentiation. Transient transfection assays of mouse skeletal muscle cell lines with DNA constructs containing MLC1A promoter fragments fused to the chloramphenicol acetyltransferase (CAT) gene show that the first 630 bp of the promoter is suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 63 publications
(71 reference statements)
5
77
0
Order By: Relevance
“…32 Myl4, another regeneration marker overexpressed in the mouse models here studied, is related to myotube formation, as it is transcribed in skeletal muscle during the start of muscle differentiation. 33 Tnnt2, coding for troponin type 2, is also expressed at the beginning of regeneration and was found overexpressed in DMD patients, which was associated with the active regeneration in dystrophic muscle. Figure 5 Enriched functional categories.…”
Section: Characterization Of the Dystrophic Processmentioning
confidence: 99%
“…32 Myl4, another regeneration marker overexpressed in the mouse models here studied, is related to myotube formation, as it is transcribed in skeletal muscle during the start of muscle differentiation. 33 Tnnt2, coding for troponin type 2, is also expressed at the beginning of regeneration and was found overexpressed in DMD patients, which was associated with the active regeneration in dystrophic muscle. Figure 5 Enriched functional categories.…”
Section: Characterization Of the Dystrophic Processmentioning
confidence: 99%
“…Li et al (41) further demonstrated that deletion of a region containing two CArG boxes in the mouse SM22␣ gene (another highly specific SMC marker) resulted in a significant drop in transcriptional activity in cultured SMCs. Thus, similar to several cardiac-and skeletal muscle-specific genes (42)(43)(44), CArG-SRF interaction appears to serve as a common transcriptional activation mechanism for multiple SM-specific genes.…”
Section: Carg Boxes 1 and 2 Function As Recognition Sites For Srf Or mentioning
confidence: 99%
“…Because the G-to-A 3Ј-end divergence in MyoD-CArG is similar to that reported previously in MLC1A-CArG-box, shown to be functional in binding SRF (Catala et al, 1995), we investigated whether MLC1A-CArG also binds MEF2 proteins during differentiation. Anti-MEF2 supershift experiments with MLC1A probe show that MLC1A-CArG only bound SRF but not MEF2 proteins ( Figure 2B, right lanes).…”
Section: Myod-carg Element: a Unique Hybrid Sequence Composed Of Bindmentioning
confidence: 88%
“…Interestingly, a divergent CArG sequence in MLC1A gene, described as functional (Catala et al, 1995), contains the same 3Ј G-to-A divergence as the MyoD-SMB element. In addition, the decanucleotide core sequences are identical in both cases, with the exception of one nucleotide divergence (A to T) in the A/T tract of MLC1A CArG.…”
Section: Myod-smb Element Is a Unique Hybrid Sequence Capable Of Bindmentioning
confidence: 99%